MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DI MA ANWARUL HASANIYYAH (ANWAHA) KABUPATEN TABALONG - Annisa Kartika Dewi; Fitri Yani; Hayatun Nida; Syahrani Syahrani (ADIBA : JOURNAL OF EDUCATION, 2023)
The principal is a person who has a big influence in a school. As a manager, the principal plays a role in managing the educational resources they have. The principal must be able to bring change to the school he leads to become a quality school by utilizing resources, especially teachers. Teachers are required to master pedagogical, professional, social and personality competencies, for this reason the real role of school principals is needed to improve teacher competency. This research aims to determine the role of the school principal as a manager in determining strategies through collaboration and communication at the MA Anwarul Hassaniyah (ANWAHA) school in Tabalong Regency from the aspects of planning, organizing, mobilizing and supervising. This research uses quantitative methods and data collection techniques using observation and interviews. The principal of the MA Anwarul Hassaniyah (ANWAHA) Tabalong school has carried out his role as a manager by implementing management principles which include Planning, Organizing, Mobilizing, Supervising.